Characteristics of Domestic Violence in the Context of Divorce Legal Formulation of the Religious Chamber in SEMA No. 3 of 2023 - Masyayih, Ali Akbar; Al Waris, Mohammad Wahyu; Rato, Dominikus (Istinbath : Jurnal Hukum, 2024)
This research aims to analyze the resolution of divorce disputes in religious courts after the implementation of Circular Letter of the Supreme Court of the Republic of Indonesia Number 3 of 2023 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Court Chamber of the Supreme Court in 2022 as a Guide to the Implementation of Duties for the Court. The method used for this research is a normative legal research method which refers to literature and legal research, then data collection and analysis is carried out after which conclusions are drawn using deductive thinking methods. The results of the study show that, the publication of the Religious Chamber's Formulation of Circular Letter Number 3 of 2023 which regulates that to maintain a marriage and fulfill the principle of making divorce difficult, divorce cases based on continuous disputes and quarrels can be granted if it is proven that the husband/wife has continuous conflicts and quarrels. continuously, or have been separated from their residence for at least 6 (six) months, it does not just appear out of thin air but goes through a long process. The Supreme Court through the Religious Chamber Meeting Formulations in SEMA 4 of 2014 also provided several indicators indicating the condition of a broken household ( broken marriage ). This formulation was then refined in SEMA 3 of 2023 which provides instructions for judges to consider sufficiently and carefully when adjudicating divorce cases. The formulation of the Religious Chamber Meeting in SEMA 3 of 2023 emphasizes the provisions of Article 39 paragraph (2) of Law Number 1 of 1974 concerning Marriage, which makes it easier for judges to explore the roots of divorce problems submitted by husbands or wives to minimize the reasons for divorce, continuous disputes and quarrels